Continuous intention to use E-wallet in the context of the COVID-19 pandemic: Integrating the Health Belief Model (HBM) and Technology Continuous Theory (TCT) - Ahmad Daragmeh; Judit Sági; Zoltán Zéman (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Personal safety has had a renewed focus throughout the COVID-19 pandemic, which has led to behavioral change. The adoption of E-wallets facilitates social distancing and thereby helps prevent the spread of the COVID-19 virus. This paper aims to investigate the potential for consumers' continued usage of an E-wallet service through an integrated framework based on two established models: the Health Belief Model (HBM) and Technology Continuous Theory (TCT). An electronic survey was distributed to a sample of 1080 individuals from academic society in three different Hungarian universities who had used an electronic wallet during the pandemic COVID-19. Structural equation modelling (SEM) was applied in the study and explained the 55.9% variance in consumers' continuous intention towards E-wallet usage. This study found that while the COVID-19 pandemic strongly influenced the current use of e-wallets; the pivotal factor affecting their continued use is based on consumer self-efficacy. The study has both short and long-term implications; in the short-term, decisionmakers should utilize health threat constructs (as an element of the protective behaviors taken during the COVID-19 pandemic) to motivate consumers to use E-wallets; in the longer-term, banks should develop further strategies that encourage consumer loyalty regarding E-wallets by reassuring customers that these financial services achieve the value and benefits that they expect, resulting in self-efficacy.
Keywords: 650; e-wallet; COVID-19; technology continuous theory; health belief model; post-adoption